Hydrogen-plasma-induced magnetocrystalline anisotropy ordering in self-assembled magnetic nanoparticle monolayers - Weddemann, Alexander; Meyer, Judith; Regtmeier, Anna; Janzen, Irina; Akemeier, Dieter; Hütten, Andreas (Beilstein Journal of Nanotechnology, 2013)
Self-assembled two-dimensional arrays of either 14 nm hcp-Co or 6 nm ε-Co particle components were treated by hydrogen plasma for various exposure times. A change of hysteretic sample behavior depending on the treatment duration is reported, which can be divided in two time scales: oxygen reduction increases the particle magnetization during the first 20 min, which is followed by an alteration of the magnetic response shape. The latter depends on the respective particle species. Based on the Landau–Lifshitz equations for a discrete set of magnetic moments, we propose a model that relates the change of the hysteresis loops to a dipole-driven ordering of the magnetocrystalline easy axes within the particle plane due to the high spatial aspect ratio of the system.
Keywords: dipolar particle coupling; magnetic nanoparticles; magnetocrystalline anisotropy; monolayers